Genital and anal injuries: A cross-sectional Australian study of 1266 women alleging recent sexual assault - Zilkens, R.; Smith, D.; Phillips, M.; Mukhtar, S.; Semmens, James; Kelly, M. (Elsevier Ireland Ltd, 2017)
© 2017 The AuthorsObjectives To describe the frequency of genital and anal injury and associated demographic and assault characteristics in women alleging sexual assault. Design Cross-sectional study. Setting Sexual Assault Resource Centre (SARC), Western Australia. Participants Total of 1266 women attending SARC from Jan-2009 to Mar-2015. Methods Women underwent a standardised data collection procedure by forensically trained doctors. Multivariate logistic regression analyses were performed. Main outcome measures (1) Frequency of genital and anal injuries by type of sexual assault. (2) Identification of independent factors associated with genital and anal injuries following, respectively, completed vaginal and anal penetration. Results Genital injury was observed in 24.5% of all women with reported completed vaginal penetration; in a subset with no prior sexual intercourse 52.1% had genital injury. Genital injury was more likely with no prior sexual intercourse (adjusted odds ratio [adj. OR] 4.4, 95% confidence interval [95%CI] 2.4–8.0), multiple types of penetrants (adj. OR 1.5, 95%CI 1.0–2.1), if general body injury present and less likely with sedative use and delayed examination. Anal injury, observed in 27.0% of reported completed anal penetrations, was more likely with multiple types of penetrants (adjusted OR 5.0, 95%CI 1.2–21.0), if general body injury present and less likely with delayed examination. Conclusion This study separately quantifies the frequency of both genital and anal injuries in sexually assaulted women. Genital injuries were absent in a large proportion of women regardless of prior vaginal intercourse status. It is anticipated that findings will better inform the community, police and medico-legal evidence to the criminal justice system.